Lifestyle profiling : Using retail brand as a priori / Sofiah Abd. Rahman - Abd. Rahman, Sofiah (Universiti Teknologi MARA Cawangan Pahang, 2004)
Market identification calls for the right segmentation base. Hence, research works should be undertaken to test the usefulness of other variables in painting a picture of the consumer. Because merchandise uniqueness has become one of the most defining criteria of a successful retail store and since retail brands are the main source of creating this uniqueness, consumer retail brand lifestyle orientation is taken as the variable to be ‘experimented’. As the first step to grouping customers, factor analysis was applied to the 14 retail brand statements (posed to the respondents) to determine the possible retail brand dimensions. At the end, the researcher’s attempt to draw out a number of factors underlying the input variables was unsuccessful. A startling insight of the meaning of retail brands from the consumer’s perspective was uncovered and could be the cause to this unsuccessful attempt.